Knowledge, perceptions and attitude of women about cervical cancer and its screening in Iyin Ekiti, Ekiti State, Nigeria: 10.55131/jphd/2023/210116 - Amu, Eyitope; Ajayi, Paul; Solomon, Oluremi; Odu, Olusola (Journal of Public Health and Development, 2022)
In Nigeria, cervical cancer is a leading cause of morbidity and mortality among women. This study was conducted to determine women’s knowledge, perceptions and attitude to cervical cancer and its screening services in Iyin-Ekiti, South-Western Nigeria. A community-based, cross-sectional study was used. An interviewer-administered, semi-structured questionnaire was used to elicit information from 397 women of reproductive age who were recruited using the multistage sampling technique. SPSS version 20 was used for statistical analysis at univariate and bivariate levels. The level of statistical significance was set at p-value ≤ 0.05. Only 182 (45.8%) respondents were aware of cervical cancer. Among those aware, 78 (42.9%) had poor knowledge, and 85 (46.7%) had both poor perception and negative attitude toward cervical cancer screening. Age (p=0.001), marital status (p=0.001), ethnicity (p=0.001), religion (p=0.04), employment status (p=0.001), monthly income (p=0.001) and educational status (p=0.005) were associated with knowledge of cervical cancer. Religion (p=0.004) and monthly income (p=0.001) were associated with attitudes to cervical cancer screening. The study concluded that there is a huge gap in awareness level and knowledge level, with about half of the respondents showing poor perception and attitude towards cervical cancer and its screening among women of reproductive age group in this region. Community-based health education about cervical cancer and social mobilization for its screening is urgently required among women of reproductive age.